2015
DOI: 10.1016/j.jhep.2015.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Expression and functionality of Toll- and RIG-like receptors in HepaRG cells

Abstract: Our results indicate that HepaRG cells express a similar pattern of functional TLR/RLR as compared to PHH, thus qualifying HepaRG cells as a surrogate model to study pathogen interactions within a hepatocyte innate system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
74
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 38 publications
3
74
0
1
Order By: Relevance
“…To investigate the mechanisms of induction of inflammatory signaling by HCV proteins, we used HepaRG cells, which are human hepatocyte progenitors closely related to primary cells, notably with respect to their fully functional immune signaling network (32,45,46). Since we have previously shown that the viral polymerase triggers inflammatory signaling in hepatocytes (12), we now analyzed its effects on the level of expression of several cellular PRRs (i.e., RIG-I, MDA5, TLR3, TLR9, NOD1, and NOD2).…”
Section: Ns5b Increases Nod1 Expression and Activates Its Downstream mentioning
confidence: 99%
“…To investigate the mechanisms of induction of inflammatory signaling by HCV proteins, we used HepaRG cells, which are human hepatocyte progenitors closely related to primary cells, notably with respect to their fully functional immune signaling network (32,45,46). Since we have previously shown that the viral polymerase triggers inflammatory signaling in hepatocytes (12), we now analyzed its effects on the level of expression of several cellular PRRs (i.e., RIG-I, MDA5, TLR3, TLR9, NOD1, and NOD2).…”
Section: Ns5b Increases Nod1 Expression and Activates Its Downstream mentioning
confidence: 99%
“…Initial studies demonstrated that these chemokines were mainly produced after an adaptive immune response (11)(12)(13). However, more recent studies have shown that HBV can also stimulate production of chemokines such as CXCL10 at early time points (14)(15)(16). Unfortunately, antiviral innate immunity against HBV that occurs minutes after virus contact is an area that has been neglected and necessitates further investigation.…”
mentioning
confidence: 99%
“…The analysis of the implication of ISGs in an anti-HBV phenotype in vitro is rendered difficult by the fact that IFN-is a not a very potent inhibitor of HBV replication in relevant cell culture models, including primary human hepatocytes (PHH) and the HepaRG cell line. Those models are relevant because there are functional for innate functions in contrast to hepatoma cells (Luangsay et al, 2015). In our hands, only a 50% reduction of the intracellular total HBV DNA accumulation is observed with a single Mao et al, 2013;Nguyen et al, 2007), following experiments in transfection, have yet to be confirmed.…”
Section: Modes Of Action Of Ifn-mentioning
confidence: 64%